Ciudadanía Global y Pobreza. Estudio exploratorio de las narrativas de futuros docentes en Cantabria (España) y propuestas para reorientar su formación - Adelina Calvo-Salvador; Carlos Rodríguez-Hoyos; Elia Fernández-Díaz (Revista Iberoamericana de Estudios de Desarrollo, 2023)
In this paper, it is presented the results of a descriptive exploratory study with which it is aimed to understand what previous conceptions future Infant and Primary Education teachers in Cantabria have regarding three central issues in the Global Citizenship Education approach (GCE). These are: a) what is «global citizenship» and what are the characteristics of a «global citizen», b) conceptions of poverty in a globalised world, and c) what role should education have in addressing these realities? The study was conducted over two academic years and 248 responses were analysed following the application of an open-ended questionnaire. Our objective is to understand the previous perceptions of these future teachers, to expand and challenge them, in the second phase, through the development of GCE projects in their university degrees. We understand GCE from the perspective of critical pedagogy and we are focused on developing a challenging university curriculum, which allows the discussion of topics linked to how globalisation affects our lives.